Economic development of the Russian Federation’s regions: factor-cluster analysis - Piskun, E.I.; Khokhlov, V.V. (Ekonomika regiona, 2019)
The economics of the Russian Federation is characterized by imbalanced social-economic development of its regions. For assessing the local regional imbalances we used the methods of multidimensional classification along with the methods of convergence analysis: methods of factor analysis, cluster analysis, discriminant analysis. The article offers to use exploratory factor analysis to cluster the Russian Federation’s regions. This method allows performing the procedure of classification structures’ identification when there is a large number of classification’s objects described by dozens of variables each. We checked the hypothesis that at a definite moment or period of time each region is described by some set of interconnected variables. This interconnection occurs due to exploratory factors which make these valuables interconnect in the necessary way. The model of exploratory factor analysis describes this situation. The basis of our research was the official Rosstat’s statistics for the period from 2014 to 2016. This specific period is characterized by changes in Russia’s spatial organization as two federal subjects, the city of Sevastopol and the Republic of Crimea, were included. As a result of calculations three exploratory factors have been defined: the first one encourages the usage of natural resources to form the gross regional product; the second one is interpreted as the factor that is not promoting the economic growth; the third one indicates the necessity to develop activity which is not connected with natural resources. We have distinguished eight economic clusters of subjects of three federal districts and have defined the character of the exploratory factors’ influence. The results of this research can be taken into account by the federal authorities during the comparative analysis of the economic development of the Russian Federation’s subjects, and formation of a developing strategy of the whole country in general and each subject in particular.